Optimal OCR setting and protection coordination on priority customer feeder at PT. PLN ULP Gondang Wetan using modified firefly algorithm - Gaol, Hans Hanggara Lumban; Pujiantara, Margo; Priyadi, Ardyono (Edelweiss Applied Science and Technology, 2025)
Reliability and continuity of electricity supply are vital for priority customers such as hospitals and other critical facilities. Overcurrent relays (OCR) play a key role in detecting overcurrent and preventing further system damage; however, proper coordination between main and backup relays is crucial to maintain protection efficiency. This study aims to optimize the Time Dial Setting (TDS) and OCR protection coordination using the Modified Firefly Algorithm (MFA) in the distribution system of PT. PLN ULP Gondang Wetan. MFA was implemented in MATLAB to determine optimal relay parameters, while ETAP software was used to verify Time-Current Characteristic (TCC) curves. Several IEEE characteristic curves, such as Normal Inverse, Very Inverse, Long-Time Inverse, and Extremely Inverse, were evaluated. Results show that MFA generates optimal TDS settings, improves relay coordination, reduces operating time, and produces Coordination Time Interval (CTI) values that fulfill the required criteria for protection selectivity. This method offers a systematic framework for optimizing OCR settings in Indonesian industrial power systems, reducing service interruptions and enhancing supply continuity for critical customers.